2020
DOI: 10.1002/bsl.2450
|View full text |Cite
|
Sign up to set email alerts
|

Motivational pathways underlying the onset and maintenance of viewing child pornography on the Internet

Abstract: The staggering rate at which incidents of child pornography (CP) are increasing highlights the need for proactive approaches to this problem. Improving the efficacy and accessibility of interventions designed for individuals who view CP provides one means of addressing this growing concern. This article explores the self‐identified motivations underlying the onset and maintenance of viewing Internet‐based CP among a sample of 20 men receiving treatment for this behavior. Our findings suggest two primary motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…More research would be useful in relating the roles of tolerance and escalation in the PUP of viewers who escalate to viewing child abuse material. This seems to have become a wide and growing aspect of cybercrime around the world [43,44]. More knowledge of effective crime-fighting strategies could lead to better policy-making on prevention and to better risk-based advice for the courts and judges around sentencing and disposal.…”
mentioning
confidence: 99%
“…More research would be useful in relating the roles of tolerance and escalation in the PUP of viewers who escalate to viewing child abuse material. This seems to have become a wide and growing aspect of cybercrime around the world [43,44]. More knowledge of effective crime-fighting strategies could lead to better policy-making on prevention and to better risk-based advice for the courts and judges around sentencing and disposal.…”
mentioning
confidence: 99%
“…In considering the neighboring field of CSAM engagement, Knack et al (2020) suggested elements of habituation and compulsion. The time periods between offenses suggested that an element of compulsion may feature among the present sample; however, there was a notable difference between the two primary clusters.…”
Section: Discussionmentioning
confidence: 99%
“…To do this, we employed the elbow method (Maheswari, 2019) to identify how many latent clusters were present in these data; we then confirmed this number using the gap statistic (Maheswari, 2019;Tibshirani et al, 2001). With the optimal number of clusters identified, we then employed k-means for analysis (Amer, 2020;Jain & Dubes, 1988).…”
Section: K-meansmentioning
confidence: 99%
“…Recently, the purported availability of CEM on popular mainstream pornography websites has attracted media attention [28]. The potential for popular genres of ostensibly legal pornography, such as the category of "teen", to represent a stepping stone or gateway to CEM offending has been recognised [29,30]. Moreover, a growing number of qualitative studies with CEM offenders suggest that it is not uncommon for onset-the first deliberate viewing of CEM [31]-to begin following initial inadvertent exposure to CEM while searching for adult pornography [32,33].…”
Section: Cem Education For Deterrencementioning
confidence: 99%